Zur Eindeutigkeit der Kristallstrukturanalyse - Peter Engel (CHIMIA)
The phase problem of the crystal structure analysis is explained in the Fourier- and Patterson space and the occurance of homometric structures is demonstrated. Assuming complete separation in the Pattersonsynthesis a theorem about the uniqueness of the crystal structure analysis in the nonpolar space groups is formulated. Consequences of this theorem are shown through examples and the crystal structure analysis is critically discussed.